Vulneración del derecho al acceso a la justicia sobre el emplazamiento a las partes, en el juzgado penal colegiado supraprovincial de la corte superior de justicia de Loreto, año 2020 – 2021 - Chumbe Silva, José Neil (2024)
The objective is the effective location of the parts of the Caballocoha district, it would improve the access to justice of the parties, in the Supraprovincial Collegiate Criminal Court of Loreto, year 2020 to 2021. The specific objectives were: Specify the causes for which, there is no effective location of the procedural parties within the district of Caballococha. Investigate to what extent compliance with the second paragraph of article 355 of the Criminal Procedure Code can be made possible. Specify whether effective compliance with the procedural parties in the districts of the Province of Ramón Castilla improves access to justice for these procedural parties, avoiding judicial delays. The type of research was quantitative - transversal, and due to its study, it is dogmatic research and dogmatic study, since it studies the content of the access of an effective summons to the procedural subjects who are going to attend the plenary session of the oral trial, the same that we address in the research. Thus, it can be stated that the failure to summon the parties to the collegiate courts violates the right of the procedural subject in the collegiate criminal courts during the year 2020 - 2021.